The building of strategic capabilities for sustainable competitive advantage : case studies in the New Zealand seafood industry : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Strategic Management at Massey University, Albany, New Zealand - Bess, J Randall (Massey University, 2001)
The aim of this study was to identify the process by which selected New Zealand seafood firms built firm-specific resources, referred to as strategic capabilities, to gain and sustain a competitive advantage in the context of New Zealand's economic reforms and transformation of the fisheries management system. Having identified several contextual factors unique to the seafood industry and the macro-environment, this study examined the capabilities building process using broad organisational, environmental and historical contexts. A case study approach was used to conduct the research. The case study design consisted of four medium to large-sized, highly vertically-integrated seafood firms. Data were collected from interviews, internal documents, industry documents and observations. The study concludes that the strategic capabilities building process is predominantly systemic, that is utilising and combining several firm-specific resources to develop simultaneously sources of advantage so that firms can compete successfully in the highly competitive international seafood market. The systemic nature of the strategic capabilities building process requires seafood firms to build up intangible processes and routines that link all of their value chain activities in the best possible way. Processes and routines are dynamic; they change, therefore, with the acquisition and integration of new knowledge about a firm's operations, its products and those external environmental forces that impact on the firm. This study suggests that the greatest potential gain for highly vertically-integrated firms lies in senior managers' reviewing the nature and extent of their interactions, their comprehension of value chain activities, and their firm-wide communication-oriented processes and routines that support the capabilities building process. This study also confirms that for vertically-integrated firms operating in resource-based industries, secure access rights to the resource play a critical role in firm-level competitiveness.
Keywords: Seafood industry; Strategic management; Competitive advantage; New Zealand; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management